Transcranial magnetic stimulation in cocaine use disorder and the risk of seizure: a review of the evidence - Imperio, Caesar G.; Parmon, Eric; Steele, Vaughn R.; Blevins, Derek; Chalme, Rebecca; Wai, Jonathan M.; Brady, Kathleen; Heilig, Markus; Hanlon, Colleen A.; Levin, Frances R.; Martinez, Diana (Frontiers in Psychiatry, 2026)
Transcranial magnetic stimulation (TMS) has emerged as a promising intervention for cocaine use disorder (CUD). However, a key concern when employing TMS in CUD is the potential risk of seizures. Our goal was to assess seizure risk in individuals with CUD undergoing TMS and to propose parameters that could mitigate it. Our review of the literature indicated that seizures are primarily associated with high-dose cocaine use necessitating urgent medical care – and that the risk is likely low outside of this setting. Thus, to mitigate potential seizure risks during TMS sessions, we suggest an assessment of recent cocaine use and an evaluation for cocaine toxicity. Additionally, rechecking motor threshold levels during treatment with TMS is recommended, especially if patterns of cocaine use change. Previous studies of TMS in CUD reported on two seizures that were linked to recent cocaine use rather than proximity to TMS treatment itself. Future research should document the timing of cocaine use relative to TMS sessions to further ensure the safety of this therapeutic approach.